2016
DOI: 10.1111/fme.12195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraspecific hybridisation between two hatchery‐reared strains of Atlantic salmon, Salmo salar, on juvenile survival and fitness‐related traits

Abstract: Intraspecific hybridisation may result in hybrid offspring exhibiting superior (heterosis) or inferior (outbreeding depression) fitness relative to their parental populations. As both have been demonstrated in salmonids, consequences of interbreeding between divergent populations are relevant to their conservation. Atlantic salmon Salmo salar L. were extirpated from Lake Ontario by the late 19th Century due to anthropogenic causes. Multiple allopatric populations of hatchery‐reared Atlantic salmon are being st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
(140 reference statements)
1
6
0
Order By: Relevance
“…differences of egg quality explain many of the results), there were no signs of outbreeding depression visible in F 1 generation crosses of landlocked salmon with anadromous salmon. This is consistent with a similar study by Audet et al (2017), who crossed anadromous and landlocked salmon without finding signs of outbreeding depression in F 1 generation. Careful evaluation of the long-term success of the hybridization crosses and backcrosses will, however, be required in the future since outbreeding depression may still become apparent only in later life-history stages or in subsequent generations (e.g.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…differences of egg quality explain many of the results), there were no signs of outbreeding depression visible in F 1 generation crosses of landlocked salmon with anadromous salmon. This is consistent with a similar study by Audet et al (2017), who crossed anadromous and landlocked salmon without finding signs of outbreeding depression in F 1 generation. Careful evaluation of the long-term success of the hybridization crosses and backcrosses will, however, be required in the future since outbreeding depression may still become apparent only in later life-history stages or in subsequent generations (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Gharrett et al 1999;McGinnity et al 2003;Gilk et al 2004). A possible caveat of our study is that outbreeding depression resulting from deleterious interactions among homozygous loci or disruption of co-adapted gene complexes may not become visible before F 2 generation (Edmands 2007;Whiteley et al 2015;Audet et al 2017).…”
Section: Discussionmentioning
confidence: 93%
“…They can be potential candidates for enclosed common-environment studies to determine their fate under target wild conditions. Researchers have studied the consequences of stocking multiple strains of Atlantic salmon Salmo salar and assessed the correlation between genetics and reproductive quality in their broodstock [27]. Although the results showed no signs of outbreeding depression in the F1 generation, research on the fate of F2 back-crosses and subsequent generations would be of value, because previous studies have suggested that outbreeding depression is an outcome of intrinsic factors (factors influenced by genotypes), which are most likely to manifest in the F2 generation or later, when the original parental genomes on the same chromosome are subjected to recombination [27].…”
Section: Genetic Analysis Of the Progeny Groupsmentioning
confidence: 99%
“…Heterosis is not considered detrimental to conservation efforts, especially when it is undertaken using different populations within species with same chromosome numbers, which leads to the production of fertile offspring. The primary aim of selecting potential populations should be to avoid the outbreeding depression that may result from cross-breeding populations with fixed chromosome differences originating from different environments for over 20 generations or with no gene flow for over 500 years [26,27]. To avoid outbreeding depression when more than one population is used for restocking, it is best to choose parent populations that show low genetic divergence and are derived from similar local habitats [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…This strategy does require the recognition that there is the potential for outbreeding depression between distant populations of the focal species when multiple source populations are used, which can often manifest in second or third generations of outbreeding. For example, outbreeding depression was detected in Slimy Sculpin (Cottus cognatus) when reintroduced to part of its historical range (Huff et al 2011; but also see Audet et al 2017).…”
Section: Source-population Selectionmentioning
confidence: 99%